Belajar Berdialog dari Yesus: Kajian Reflektif-Eksploratif dari Yohanes 4:7–21 Mengenai Perjumpaan Antariman - Adrianus Yosia (Veritas : Jurnal Teologi dan Pelayanan, 2022)
This article discusses an explorative proposal for inter-faith dialogue based on the life of Jesus amid the development of religious and tribal diversity in the city in Indonesia. The rising migration and urbanization will bring diversity to a new height in Indonesia. Hence, dialogue is a must amid the irresistible context. This proposal for dialogue will be based on Kevin J. Vanhoozer's dramatic method through the fusion of horizons which proposes how to apply biblical passages to everyday life. The reflective-explorative study of John 4:7–21 resulted in three recommendations as a form of horizon fusion in the context of ethnic and religious pluralism in the city, namely: the dialogue of reconciliation, the dialogue of friendship, and the dialogue of theology.